Financial Literacy Workshop to Intervene Consumption Patterns of Rural Areas in Malang - Soseco, Thomas; Wijayanti, Febry; Prastiwi, Lustina Fajar; Dwiputri, Inayati Nuraini; Firmansyah, Fajar; Fanisa, Tania Putri; Qodri, Lutfi Asnan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
This study explores the economic, educational, and infrastructural challenges in Srigonco Village, Bantur District, Malang Regency, Indonesia. The village's dependence on agriculture makes it economically vulnerable, while limited educational opportunities and inadequate infrastructure further hinder development. The study emphasises the critical role of financial literacy in empowering residents to make informed financial decisions and better utilise financial services. By implementing Training of Trainers (ToT) programs, the village can enhance financial management skills and promote economic resilience. Improved financial literacy is expected to lead to increased asset ownership, participation in productive activities, and long-term economic stability, ultimately improving the quality of life for the community.